Estudio hematológico en monos cariblancos (Cebus albifrons) en condiciones de cautiverio en Colombia - Castañeda-Herrera, Fabián Enrique (2020)
The aim if this study was to carry out the blood evaluation of Cebus albifrons primates kept in captivity at the Centro de Atención y Valoración de Fauna Silvestre (C.A.V) in the city of Ibagué, Colombia. Blood (~2 ml) was drawn from the femoral or axillary veins under chemical restriction in nine males (six castrated) and five females. Results were obtained for haematocrit 40.75 ± 3.91%, haemoglobin 15.2 ± 1.4 g/dl, erythrocyte counts 5 200 714 ± 510 331/mm3, mean corpuscular haemoglobin [HCM] 29.22 ± 1.46 pg, mean corpuscular haemoglobin concentration [CHCM] 37.26 ± 0.73 g/dl, mean corpuscular volume [VCM] 78.61 ± 4.46 fl, white blood cell count 8328.6 ± 2993.7/mm3, segmented neutrophils 43.56 ± 10.31%, monocytes 28.11 ± 5.28%, lymphocytes 23.54 ± 7.45%, eosinophils 4.79 ± 1.14% and platelets 276 857 ± 71 889/mm3. There were no significant differences between males and females.